PEMANFAATAN TEKNOLOGI DALAM DUNIA PENDIDIKAN YANG BERKARAKTER DI ERA GENERASI Z - Putri Kasandra Dewi; Imas Mastoah (STIT Muhammadiyah Paciran Lamongan, 2025)
This study examines the use of technology in character-based education in the Generation Z era, against the backdrop of rapid developments in information technology and profound digital transformation in the learning system. The adoption of digital innovations such as Augmented Reality (AR), Virtual Reality (VR), and social media has changed the paradigm of education, enabling widespread access to information and immersive and adaptive learning interactions. This study aims to identify the challenges faced by Generation Z in the conventional education system and explore opportunities for technology integration to improve the quality of learning and character building through a holistic approach. The method used is a qualitative literature study, with data collection through reviewing journals, books, and other relevant sources. The results of the discussion show that the use of digital technology can create an interactive, inclusive, and innovative learning environment, which not only facilitates the transfer of knowledge but also instills ethical values, discipline, responsibility, and empathy. The implications of this study include the preparation of a learning model that supports students' intellectual and moral development, as well as offering a relevant strategic approach to face the challenges of the Society 5.0 era. The findings of this study are expected to be the foundation for the development of a more adaptive and character-based education system in Indonesia. The results of this study provide an important contribution in formulating innovative and technologically-oriented education policies for the future of the nation.